The Historical Distinction between the Qur’an and Hadith: A Critical Examination of John Wansbrough’s Revisionist Perspective by Fred M. Donner - Zulfikar, Eko; Zain, Zaki Faddad Syarif; Aini, Adrika Fithrotul; Hafizh, Azhar Amrullah (Al-Qudwah, 2025)
This article aims to critically examines the distinction between the Qur’an and Hadith in response to John Wansbrough’s revisionist-skeptical perspective on the origins of the Qur’an. Wansbrough argued that both corpora emerged from the same “sectarian” milieu and developed within a nearly identical historical timeframe. The present study addresses two primary questions: how Fred M. Donner conceptualizes the distinction between the Qur’an and Hadith, and how his arguments challenge Wansbrough’s theoretical framework. Employing a qualitative methodology with a descriptive-analytical approach, this research analyzes the principal works of both scholars to compare their arguments from textual and historical perspectives. The findings indicate that Wansbrough’s thesis lacks a robust historical foundation, as six key aspects religious and political authority, portrayals of the Prophet’s contemporaries, elements of anachronism, narratives of earlier prophets, depictions of Prophet Muhammad, and descriptions of ritual prayer reveal significant differences between the Qur’an and Hadith. These results support the conclusion that the Qur’an did not originate from the same sectarian environment as the Hadith but emerged in an earlier and distinct historical context. Consequently, the Qur’an is understood to have preceded the Hadith both chronologically and in terms of codification. This article contributes to clarifying the independence and authenticity of the Qur’an as the earliest and primary source of Islamic teaching, while enriching textual-historical scholarship in response to Western revisionist discourse concerning the origins of Islamic scripture. Abstrak: Artikel ini bertujuan mengkaji secara kritis perbedaan (distingsi) antara al-Qur’an dan hadis sebagai respons terhadap pandangan revisionis-skeptis John Wansbrough mengenai asal-usul al-Qur’an. Wansbrough menilai bahwa kedua korpus tersebut lahir dari lingkungan “sektarian” yang sama dan terbentuk dalam periode historis yang hampir bersamaan. Penelitian ini berupaya menjawab dua pertanyaan utama: bagaimana Fred M. Donner memandang distingsi antara al-Qur’an dan hadis, serta bagaimana sanggahannya terhadap konstruksi pemikiran Wansbrough. Menggunakan metode kualitatif dengan analisis deskriptif-analitis, penelitian ini menelaah karya-karya utama kedua tokoh tersebut untuk membandingkan argumentasi mereka secara tekstual dan historis. Hasil penelitian menunjukkan bahwa pandangan Wansbrough tidak memiliki dasar yang kuat secara historis, sebab enam aspek utama, yakni otoritas agama dan politik, gambaran tentang masyarakat sezaman Nabi, unsur anakronisme, kisah para nabi terdahulu, representasi Nabi Muhammad, dan deskripsi tentang ritual salat menunjukkan perbedaan yang signifikan antara al-Qur’an dan hadis. Temuan ini menegaskan bahwa al-Qur’an tidak berasal dari lingkungan sektarian yang sama dengan hadis, melainkan memiliki konteks dan kronologi kemunculan yang lebih awal. Al-Qur’an diyakini muncul lebih dahulu dibandingkan hadis, baik secara kronologis maupun dalam proses kodifikasinya. Artikel ini berkontribusi dalam memperjelas independensi dan keotentikan al-Qur’an sebagai sumber ajaran Islam, sekaligus memperkaya kajian tekstual-historis dalam menghadapi wacana revisionisme Barat terhadap asal-usul dua korpus Islam.